Who is eating quinoa?: How consumer characteristics and beliefs affect the expenditure on this functional food versus traditional staple items. Issue 2 (1st December 2021) - Morales, Luis Emilio; Higuchi, Angie
Abstract: The regular consumption of quinoa has been promoted worldwide based on its high nutritional value and health benefits. However, the industry has limited information about how consumer characteristics and beliefs about functional foods affect their expenditure on those items versus traditional staple foods. Survey data were collected in Modern Metropolitan Lima, Peru, which is a case study that presents the potential relevance that functional foods could reach as part of the population diet, when they are well established as mature products. The results indicate that household income, years of education, practicing exercise regularly, and a positive sensory appeal increase monthly expenditure on quinoa. Moreover, the more consumers consider quinoa as an expensive product, the higher is their expenditure on rice, pasta, and potato, suggesting a substitution effect between quinoa and staple foods based on relative prices and budget constraints, which are key outcomes to be considered when designing food campaigns. Practical applications: Food policies and campaigns promoting a regular consumption of foods regarded as functional, as the case of quinoa, could have a positive impact on nutrition, health, and wellbeing of a growing population with malnutrition. This study provides practical implications for both policy makers and marketers of the food industry, who could develop strategies to increase the consumer expenditure and consumption of quinoa and other functional foods through the promotion of their regular intake based on their good taste when mixed with other food items and their positive contribution to a healthy diet. Considering their higher price compared to staple foods, governments could also subsidize the consumption of functional foods among families with low disposable income, allowing all citizens to consume these products and perceive their nutritional and health benefits.